Geometrical control of the interatomic coulombic decay process in quantum dots for infrared photodetectors - Dolbundalchok, Praphasiri; Peláez, Daniel; Aziz, Emad F.; Bande, Annika (Journal of computational chemistry, 2016)
In electron dynamics calculations the interatomic Coulombic decay (ICD) process has recently been shown to take place in two vertically-aligned quantum dots (QDs). Energy emitted during the relaxation of one electron in one QD is converted into kinetic energy of another electron ejected from a neighboring QD. As the electronic structure of QDs can be controlled by their geometries, we prove here in thorough scans of the transversal and vertical QD confinement potentials’ widths that geometries are likewise control parameters for ICD. Such a comprehensive investigation has been enabled by a significant development of the calculations in terms of speed achieved among others by optimization of the grid and Coulomb interaction operator representations. As key result of this study we propose two cigar-shaped singly-charged GaAs QDs vertically aligned in the direction of their long side for a most efficient QD ICD realization useful for an infrared photodetector. © 2016 Wiley Periodicals, Inc.
Gesehen am 11.05.2020